HUBUNGAN ANTARA DUKUNGAN KELUARGA DENGAN KADAR GULA DARAH PASIEN DIABETES MELITUS TIPE 2 DI PUSKESMAS - Desak Putu Pebriantini (Coping: Community of Publishing in Nursing, 2014)
Diabetes Mellitus Type 2 (DM Type 2) is a group of metabolic diseases that caused by the abnormality of insulin resistances, 90-95 % of DM cases were DM Type 2. The main goal of diabetes mellitus management is to norm the insulin activity and blood glucose level to avoid the chance of complication. The efforts that should be done in avoiding the complication of DM Type 2 are therapeutic control, correct treatment and well-arranged media control. DM Type 2 management needs an optimal social support from family to make the blood glucose level in the normal point. This study aimed at knowing the correlation between family supports with the type 2 diabetes mellitus patients’ blood glucose level in Puskesmas II Denpasar Barat. It used quantitative type of research and cross sectional study model approach. The sampling methods used non-probability sampling with purposive sampling technique resulting 55 research subjects. The data collection of family support used HDFFS (Hanserling Diabetes Family Support Scale) questionnaire that already valid and reliable, and for the blood glucose level used clinical check-up with glucose test. Based statistic test on Spearman Rank (?=0.05), it showed correlation coefficient (r) = -.638 with p=0.000 (p<?) which meant the family support and blood glucose level indicated strong with negative direction relations. The conclusion of this study indicated the correlation between family supports with blood glucose level. The suggestion of this study is collaborating family supports in giving nursing treatment to make DM Type 2 management more optimally.